Penghematan Pajak Melalui Penyajian Laporan Keuangan Entitas Berorientasi Non-laba di Indonesia - John Pieter john (Publikasi Indonesia, 2022)
Non-profit oriented (non-profit) entity is an entity that is engaged in public service that does not aim to make a profit. These non-profit oriented entities are usually established by the public or managed by the private sector. There are many forms of non-profit entities in Indonesia, one of which is the Perhimpunan Pemilik dan Penghuni Satuan Rumah Susun (P3SRS). P3SRS is formed as a representative of the owners and residents of the apartment to maintain the shared building, and other administrative tasks required as part of the occupancy obligations in the apartment area. Although the goal is not to make a profit, an excess difference between income minus expenses can occur, and can result in income tax payable. This research was conducted to find out how to save income tax payable through the presentation of financial statements by combining the applicable Financial Accounting Standards and related tax regulations. This research is a qualitative research using the case study method in the process of presenting the Financial Statements of P3SRS Maju Jaya Apartments for the 2018 period with a comparison in 2017. The data source comes from primary data in the form of interviews and secondary data in the form of P3SRS internal data. The results of the study indicate that the application of accounting and tax policies through the preparation of financial statements can save the tax burden on income.